A new species of the subgenus Bryodemella (s. str.) Yin, 1982 from Gansu, China (Orthoptera: Acridoidea: Oedipodidae) - Zhang, Yu-Long; Wang, Wen-Qiang; Yin, Zhan (Zootaxa, 2025)
A new species Bryodemella sunanensis sp. nov. of the genus Bryodemella Yin (Orthoptera, Acridoidea, Oedipodidae) from Gansu, China is described in this paper. The new species is similar to Bryodemella (s. str.) elegans Li, 1997, but differs from the latter by: anterior margin of pronotum protruding in the middle, tegmina longer, reaching to the middle of hind tibiae, hind femur without red on inner side, hind tibiae yellow on inner side and hind wing pale yellow at base part. The type specimens are deposited in the Museum of Hebei University (MHU), China.